Informal sector in economic development: An analytical foundation - Bhattacharya, Prabir (Switzerland Springer, 2024)
This book bridges the gap between theoretical and empirical understandings of the informal sector to provide insight into the role of the informal sector within the development process. By analysing three economic sectors, it sets out a framework for analysing urbanisation, rural-urban migration, agriculture- industry relationship, income inequality, structural change, employment, and optimal growth. Through highlighting the economic contribution of the informal sector, its impact on the national output and influence on the labour market is shown, alongside how employment opportunities in the informal sector drive rural and urban migration.
Keywords: Economic Development; Analyzing urbanization; Income inequality